Effect of bonding materials on the flexural improvement in RC beams strengthened with SNSM technique using GFRP bars. (November 2020) - Hosen, MdAkter; Jumaat, MohdZamin; Alsubari, Belal; Sulong, N.H. Ramli; Ibrahim, Zainah; Alengaram, U. Johnson; Hashim, Huzaifa
Abstract: In this paper, the effectiveness of cement mortar as bonding materials in the strengthening of reinforcements and concrete surface for flexural improvement of reinforced concrete (RC) beams were investigated. Recently, side near surface mounted (SNSM) and existing near surface mounted (NSM) techniques with glass fiber reinforced polymer (GFRP) bars are adopted as the strengthening methods for RC beams in which varieties of epoxy adhesive were replaced with cement mortar. In this study, one control and seven strengthened beams were tested under four-point loading in a static condition. The load-carrying capacities, failure modes, deflection, strains characteristic, parametric study and energy absorption capacities are addressed through laboratory experiments. The results revealed that the flexural performance was successfully achieved by using cement mortar as a replacement for adhesive. The SNSM strengthening technique exhibited better structural performance compared with the existing NSM technique in all aspects. Highlights: Mortar used to replace epoxy for strengthening of RC specimens as a bonding agent. First cracking and ultimate load increase of 126% and 92% by the SNSM technique. SNSM strengthened beams failed by flexure until 75% replacement of epoxy by mortar. 50% and 75% replacement epoxy by mortar in NSM beams failed by debonding. SNSM technique shows more effectiveness compared with the existing NSM technique.